ROOT PATTERNS OF THOUGHT IN LAW: A META-JURISPRUDENCE" OF PIETERSEN: A CRITIQUE AND DEVELOPMENT IN LAW - Sinaga, Henry Dianto P.; Samekto, FX Adji; Emirzon, Joni (Scientium Law Review (SLR), 2023)
The four fundamental patterns of knowledge, consisting of objectivist-idealist jurisprudence, objectivist-realist jurisprudence, subjectivist-realist jurisprudence, and subjectivist-idealist jurisprudence, are formed within the meta-paradigmatic framework proposed by Herman J. Pietersen, are still based on certain Western philosophical ideas. However, the essence of this framework is to answer the fundamental question of "how shall we live," and its meta-paradigmatic analysis is not only based on certain Western philosophies. It is concluded that the development of the various branches of law today does not only adopt these four basic patterns, as they apply very well only to legal branches such as legal naturalism and doctrinal law, legal positivism, legal expressivism, pragmatic legal realism, and CLSM. However, some legal streams related to certain philosophical and paradigmatic streams still need to be characterized by their basic knowledge patterns. Some of these legal streams include legal feminism, which is closely related to feminist philosophy, legal hermeneutics, which is closely related to hermeneutic philosophy, legal post-positivism, which is closely related to post-positivism paradigm, legal constructivism, which is closely related to constructivism paradigm, and the idea of progressive law. It is expected that in the future, there will be in-depth research on both Eastern and Western philosophical streams, which are essentially firmly related to meta-jurisprudence.